The Urgency Trap: Channeling FoMO into Impulsive Purchases Through Flash Sales in Social Commerce - Sonia Setyowati, Rifka; Agus Atmawijaya,; Nur Muhammad Kosim,; Abdul Cholida,; Popy Novita Pasaribu, (Jurnal Manajemen, 2026)
The rapid growth of social commerce in Indonesia has driven an increase in digital promotions that trigger consumptive behavior, but previous studies have mostly focused on general consumers and ignored the influence of socio-economic context on the psychological responses of low-income consumers. This research gap indicates that there has been no study specifically analyzing how FoMO and flash sale mechanisms influence impulsive buying among lower-middle-class consumers, who have financial limitations but are highly exposed to aggressive social commerce promotions. This study fills this gap by examining the role of FoMO and the mediation of flash sales using the Stimulus–Organism–Response (S-O-R) model on 391 cosmetics consumers with incomes below five million rupiah in the city of Bogor. The results show that FoMO has a very strong direct influence on impulsive buying, while flash sales act as a partial mediator that reinforces impulsive responses. These findings reveal that internal psychological factors are far more dominant than promotional stimuli alone. The unique contribution of this research lies in its focus on lower-middle-class consumers in Indonesia's social commerce ecosystem, as well as its empirical explanation of how this group's psychological vulnerability is exploited by digital promotional strategies. This study enriches the literature on digital consumer behavior in developing countries and emphasizes the need for more ethical marketing practices for vulnerable groups.